The disruptive Savannah Bananas : adding a-peel to baseball - Brooks, Bradley, (SAGE Business cases., 2022)
Jesse Cole had created a college-level amateur baseball team that sold one season ticket in its first two months of existence. By the end of the first season, Jesse had turned things around as the team began selling out every home game. Within five years, Jesse had transformed the Savannah Bananas from a mundane baseball team into a disruptive entertainment experience that fans could not wait to see – while more than doubling the team’s revenue in the process. However, Jesse now faced new challenges for the team, such as how to grow the organization despite the team’s physical capacity limitations. The organization had expanded sales of merchandise, developed a strong social media presence, and added a premier team of professional players. For the Bananas, the future was full of possibilities, but the team needed concrete plans to grow the brand and the organization.